1989
DOI: 10.1002/jor.1100070112
|View full text |Cite
|
Sign up to set email alerts
|

Gain in mass density of bone following strenuous physical activity

Abstract: A group of 223 military recruits aged 18-21 years underwent strenuous physical training for a period of 14 weeks. The absolute bone density of the distal tibia in both lower limbs was measured before the training period and at its end. The density was determined by the Compton scattering technique, which has been developed in our laboratory; this method provides the bone mass of all bone constituents per unit volume. The distribution curve of the bone density in both tibiae shifted to higher values at the end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 14 publications
(3 reference statements)
2
22
0
2
Order By: Relevance
“…Thus, with respect to an optimum osteoanabolic exercise strategy, we would not advice to increase volumes of the given exercise type 3 further but to add new types of exercises in order to generate other types and distributions of strain and/or favorably impact the hormonal environment [33,34] and so additively/ synergistically enhance BMD. It is difficult to compare our results with data of available prospective physical activity or exercise studies [26,28,[35][36][37][38][39][40][41][42][43][44][45][46][47] that focus on BMD during young adulthood (17-30 years) due to the very dissimilar approach. The majority of studies either determined the effect of short, isolated, and specific exercise interventions on BMD [35, 39, 41, 43, 44, 46] 4 or accompany athletes of different disciplines (e.g., [36,37,40,45,47] in order to identify promising types of sports.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Thus, with respect to an optimum osteoanabolic exercise strategy, we would not advice to increase volumes of the given exercise type 3 further but to add new types of exercises in order to generate other types and distributions of strain and/or favorably impact the hormonal environment [33,34] and so additively/ synergistically enhance BMD. It is difficult to compare our results with data of available prospective physical activity or exercise studies [26,28,[35][36][37][38][39][40][41][42][43][44][45][46][47] that focus on BMD during young adulthood (17-30 years) due to the very dissimilar approach. The majority of studies either determined the effect of short, isolated, and specific exercise interventions on BMD [35, 39, 41, 43, 44, 46] 4 or accompany athletes of different disciplines (e.g., [36,37,40,45,47] in order to identify promising types of sports.…”
Section: Discussionmentioning
confidence: 57%
“…Only two studies [38,42] evaluated the comprehensive effect of severe occupational and life style changes on bone (military basic training). Very similar to our study, Casez et al [38] compared the effect of diverse (military) occupations that profoundly differ with respect to physical demands (e.g., "infantry" vs. "tank drivers" vs. "general store privates") on bone parameters in military recruits.…”
Section: Discussionmentioning
confidence: 99%
“…Lamin A/C haploinsufficient mice exposed to strenuous exercise demonstrated significant trabecular and cortical thinning and a reduction in osteoblasts and osteocyte numbers compared with their sedentary counterparts whilst the wild type exposed to exercise showed a significant increase in bone volume and number of bone cells. In humans, functional loading has been shown to improve bone mass [Leichter et al 1989] and exercise training programs can prevent or reverse almost 1% of bone loss per year in both lumbar spine (LS) and femoral neck (FN) for both premenopausal and postmenopausal women [Wolff et al 1999]. …”
Section: The Role Of Exercisementioning
confidence: 99%
“…However, cross-sectional data from a stratified random sample of women and men 21 to 97 years of age did not find any close correspondence between changes in habitual load and changes in bone strength [43], indicating a more complex relationship. Nevertheless, interventional trials that increase functional loading have shown positive results in improving bone mass [44]. Although most attention has been focused on bone mass and strength, the risk of nonvertebral fractures also depends on the frequency and types of falls.…”
Section: Modulation Of the Aging Skeleton By Nutrition And Lifestylementioning
confidence: 96%